Towards correlative super‐resolution fluorescence and electron cryo‐microscopy. (22nd June 2016) - Wolff, Georg; Hagen, Christoph; Grünewald, Kay; Kaufmann, Rainer
Abstract : Review : Cryo‐CLEM presents a powerful tool in the field of structural (cell) biology. However, the big resolution gap between cryo‐FM and cryo‐EM is currently hindering many biological applications. Super‐resolution cryo‐FM holds the key to this problem, but is still in its infancy. In this review, we highlight the challenges and prospects of super‐resolution cryo‐CLEM in the context of the current state of the art regarding technical and photo‐physical considerations. Abstract : Correlative light and electron microscopy (CLEM) has become a powerful tool in life sciences. Particularly cryo‐CLEM, the combination of fluorescence cryo‐microscopy (cryo‐FM) permitting for non‐invasive specific multi‐colour labelling, with electron cryo‐microscopy (cryo‐EM) providing the undisturbed structural context at a resolution down to the Ångstrom range, has enabled a broad range of new biological applications. Imaging rare structures or events in crowded environments, such as inside a cell, requires specific fluorescence‐based information for guiding cryo‐EM data acquisition and/or to verify the identity of the structure of interest. Furthermore, cryo‐CLEM can provide information about the arrangement of specific proteins in the wider structural context of their native nano‐environment. However, a major obstacle of cryo‐CLEM currently hindering many biological applications is the large resolution gap between cryo‐FM (typically in the range of ∼400 nm) and cryo‐EM (single nanometre to the Ångstrom range). Very recently, first proof of concept experiments demonstrated the feasibility of super‐resolution cryo‐FM imaging and the correlation with cryo‐EM. This opened the door towards super‐resolution cryo‐CLEM, and thus towards direct correlation of structural details from both imaging modalities.